Cost Assessment of Tourism Infrastructure Functioning in Village Commune - Maciej GLINIAK; Piotr WALĄG; Sabina WIATR (Communications of International Proceedings, 2020)
The development of tourism in rural areas is limited by the lack of financial resources. The study was conducted expertise of tourism infrastructure over the 2010-2015 years in the community of Tuchów. Shows the net cost of the sale of tourist services, net income from the sale of tourist services, subsidy budget to secure the provision of tourist services and the gain (loss) on sale of tourist services, and prepared SWOT analysis contains a number of factors significant for the development of the community. The analysis can be seen that tourism in the community is not propagated. To enrich the tourist attractiveness should modernize existing tourist facilities and to finance the creation of new attractions.
Keywords: Cost assessment; organization; infrastructure; management.